Implementation of STEM in Science Learning in Elementary Schools - Cinderella, Selvy; Amriyah, Chairul; Yanti, Yuli (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyse the trend of STEM implementation in IPAS learning in primary schools. The research method used systematic literature review. Data collection came from google scholar and publish or perish from 2023 to 2025, from 50 articles focused on reviewing 14 articles. Data were analysed by descriptive analysis. The research procedure includes planning, conducting, and reporting. The results showed that Science, Technology, Engineering, Mathematics (STEM) education has become a major focus in efforts to improve the quality of learning at the primary school level. From the analysis of 14 studies that the application of the STEM approach shows novelty in learning methods that create more relevant and interesting learning experiences by integrating local culture, technology and art. The focus on 21st century skills, such as critical thinking, creativity and collaboration, indicates the need to adapt education to the needs of the modern world of work. The application of STEM approaches in education not only improves students' conceptual understanding but also prepares them to face challenges in the digital age. This research emphasises the importance of innovation in STEM education to create more competitive and skilled students for the future.